One giant leap for mankind: can ecopoiesis avert mine tailings disasters? - Cross, Adam; Stevens, Jason; Dixon, Kingsley (Springer Netherlands, 2017)
Background: Mine tailings are among the most ecologically hostile byproducts of mining operations, with production generating alien substrates with significant cascading environmental and human welfare legacies. The rate of tailings production continues to increase globally, and this increase has occurred asynchronously with our capacity to ameliorate ecological hostility and implement successful restoration programs on tailings landforms. Scope: There is currently a lack of sufficient technology to deliver timely and cost-effective restoration outcomes to tailings landscapes. The decadal to millennial time scale of soil formation driven by natural pedogenic processes is at odds with the short mine closure timeframes (≤5 years) and aspirations of newly formulated international standards for the practice of ecological restoration. This lack of restoration capability places biodiversity at risk, and not only jeopardises the economic viability of the mining industry but also impacts upon its social and environmental license to mine. Conclusions: Delivery of successful ecosystem restoration on tailings requires a new paradigm of collaborative science-driven innovation. Could this be guided by the fundamental theory behind establishing life on other planets?